Diagnostic Accuracy of Point of Care Tests for Diagnosing Celiac Disease: A Systematic Review and Meta-Analysis. Issue 7 (August 2019) - Singh, Prashant; Arora, Ananya; Strand, Tor A.; Leffler, Daniel A.; Mäki, Markku; Kelly, Ciaran P.; Ahuja, Vineet; Makharia, Govind K.
Abstract : Goals: To perform a systematic review and meta-analysis to estimate the overall diagnostic accuracy of point of care tests (POCTs) for diagnosing celiac disease (CD). Background: Recently, POCTs for CD have been developed and are commercially available. Studies have reported significant variability in their sensitivity (70% to 100%) and specificity (85% to 100%). Study: We searched MEDLINE, EMBASE databases, and the Cochrane library through June 2017. Positive reference test was defined as villous atrophy along with positive celiac-specific serology and/or clinical improvement after gluten-free diet. Normal duodenal biopsy was defined as negative reference test. Bivariate random-effect model was used to present the summary estimates of sensitivities and specificities along with 95% confidence regions We assessed methodologic quality using the quality assessment of diagnostic accuracy studies-2 tool. Results: The pooled sensitivity and specificity of all POCTs (based on tTG or DGP or tTG+Anti-gliadin antibodies) for diagnosing CD were 94.0% [95% confidence interval (CI), 89.9-96.5] and 94.4% (95% CI, 90.9-96.5), respectively. The pooled positive and negative likelihood ratios for POCTs were 16.7 and 0.06, respectively. The pooled sensitivity and specificity for IgA-tTG-based POCTs were 90.5% (95% CI, 82.3-95.1) and 94.8% (95% CI, 92.5-96.4), respectively. Conclusions: The pooled sensitivity and specificity of POCTs in diagnosing CD are high. POCTs may be used to screen for CD, especially in areas with limited access to laboratory-based testing. Further research assessing the diagnostic accuracy of individual POCTs and comparing it with other available POCTs is needed. Abstract : Supplemental Digital Content is available in the text.